Experienced physicians benefit from analyzing initial diagnostic hypotheses - Bass, Adam; Geddes, Colin; Wright, Bruce; Coderre, Sylvain; Rikers, Remy; McLaughlin, Kevin (Revue canadienne de l’éducation médicale, 2013)
Background: Most incorrect diagnoses involve at least one cognitive error, of which premature closure is the most prevalent. While metacognitive strategies can mitigate premature closure in inexperienced learners, these are rarely studied in experienced physicians. Our objective here was to evaluate the effect of analytic information processing on diagnostic performance of nephrologists and nephrology residents. Methods: We asked nine nephrologists and six nephrology residents at the University of Calgary and Glasgow University to diagnose ten nephrology cases. We provided presenting features along with contextual information, after which we asked for an initial diagnosis. We then primed participants to use either hypothetico-deductive reasoning or scheme-inductive reasoning to analyze the remaining case data and generate a final diagnosis. Results: After analyzing initial hypotheses, both nephrologists and residents improved the accuracy of final diagnoses (31.1% vs. 65.6%, p < 0.001, and 40.0% vs. 70.0%, p < 0.001, respectively). We found a significant interaction between experience and analytic processing strategy (p = 0.002): nephrology residents had significantly increased odds of diagnostic success when using scheme-inductive reasoning (odds ratio [95% confidence interval] 5.69 [1.59, 20.33], p = 0.007), whereas the performance of experienced nephrologists did not differ between strategies (odds ratio 0.57 [0.23, 1.39], p = 0.2). Discussion: Experienced nephrologists and nephrology residents can improve their performance by analyzing initial diagnostic hypotheses. The explanation of the interaction between experience and the effect of different reasoning strategies is unclear, but may relate to preferences in reasoning strategy, or the changes in knowledge structure with experience.